2018
DOI: 10.1002/ejp.1186
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of dopamine D2 receptors disrupts intrahippocampal connectivity and enhances pain‐related working memory deficits in neuropathic pain rats

Abstract: This study provides new insights into the role of D2r in the manifestation of pain-related sWM deficits. Our findings support that selective blockade of D2r produces a significant decrease in intrahippocampal connectivity mediated by theta-oscillations, and amplifies pain-related sWM deficits. These results suggest that further characterization of intrahippocampal dopaminergic modulation may be clinically relevant for the understanding of cognitive impairments that accompanies nociceptive stressful conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Systemic application of a D2/D3 receptor agonist reversed electrophysiological and memory but not pain-related behavioral deficits in SNI rats. These deficits were exacerbated by systemic administration of a D2 receptor antagonist, which was related to a selective disruption of hippocampal theta oscillations and decrease in intrahippocampal CA1 connectivity [27]. This set of data suggests that cortico-hippocampal interactions are altered in the pain state, and that modulation of dopamine neurotransmission could be involved in these effects.…”
Section: Cortico-hippocampal Interactionsmentioning
confidence: 81%
“…Systemic application of a D2/D3 receptor agonist reversed electrophysiological and memory but not pain-related behavioral deficits in SNI rats. These deficits were exacerbated by systemic administration of a D2 receptor antagonist, which was related to a selective disruption of hippocampal theta oscillations and decrease in intrahippocampal CA1 connectivity [27]. This set of data suggests that cortico-hippocampal interactions are altered in the pain state, and that modulation of dopamine neurotransmission could be involved in these effects.…”
Section: Cortico-hippocampal Interactionsmentioning
confidence: 81%
“…Pain affects cognition in humans and rodents since it can divert attention, memory, and decision-making [64]. However, the amount of studies investigating the cognitive deficits associated with the SNI model of neuropathic pain is less than those that have focused on affective disorders [10,33,36,[65][66][67][68]. This discrepancy could reflect the complexity, number, and diversity of paradigms available for measuring cognition.…”
Section: Behavioral Symptoms Associated With the Spared Nerve Injurymentioning
confidence: 99%
“…Working memory deficits were detected in rats mainly using mazes, devices, which exploits the innate leaning (and remembering) of the location associated with safety, food or any other reward in rodents [68]. Working memory impairments were detected at 3-7 days [65] and persisted for a month [34] after SNI surgery. Additionally in rats, attention and reaction time were reduced after 1 month and 3-6 months after the SNI [42,69,70].…”
Section: Behavioral Symptoms Associated With the Spared Nerve Injurymentioning
confidence: 99%
“…It has been shown that dopamine signalling from the VTA to the NAc is markedly reduced during chronic pain (Taylor et al, 2014), which may be linked not only with comorbidities of pain but also with dysregulation of the local NAcc activation. In this regarding, we have previously reported a significant pain-related disruption of the corticolimbic connectivity during the performance of spatial WM tasks (Cardoso-Cruz, Lima, & Galhardo, 2013a;Cardoso-Cruz, Sousa, et al, 2013b;Monteiro et al, 2016), which occurred associated to an impairment of the dopaminergic signalling (Cardoso-Cruz et al, 2014;Cardoso-Cruz et al, 2018). Another important finding of this study was the fact that the peripheral nerve lesion induced a clear enhancement of spontaneous prefrontal-striatal connectivity, which is mainly mediated by theta-band activity on the ascending pathway (from NAcc to PL-mPFC; Figure 9e) and independent from the motor activity.…”
Section: Discussionmentioning
confidence: 90%